Internationalization of higher education in ukraine. Preconditions, current state, challenges - Havrilenko, Yevhen; Matsulevych, Oleksandr; Antonova, Halyna; Гавриленко, Євген Андрійович; Мацулевич, Олександр Євгенович; Антонова, Галина Володимирівна (Запоріжжя : ТДАТУ, 2024)
EN: The problems of internationalization of Ukrainian education, especially the development of the educational services market, are characterized. The priority measures of the state policy aimed at the effective realization of the educational potential of Ukraine in the context of the internationalization of the educational system are identified. UA: Охарактеризовано проблеми інтернаціоналізації української освіти, передусім, розвитку ринку освітніх послуг. Визначено першочергові заходи державної політики, спрямовані на ефективну реалізацію освітнього потенціалу України в контексті інтернаціоналізації освітньої системи.
Інтернаціоналізація вищої освіти в Україні. Передумови, сучасний стан, виклики
Keywords: higher education; internationalization; relationship development; вища освіта; інтернаціоналізація; розвиток стосунків